Scillens, Christine (audio interview #3 of 3) - Scillens, Christine (b. 1920 - ); Hobson, Brooke, interviewer
INTERVIEW DESCRIPTION - This is the last of three interviews conducted for a Women's Studies class focused on women during WWII. The interviewer and narrator knew each other from classes that they took in the American Indian Studies program. The narrator was open and willing to share her experiences, particularly because of the interviewer's known familiarity with and respect for native traditions and culture.